Positive plate and battery

By providing a lithium supplementary functional layer containing lithium platinum cube, conductive agent and stabilizer on the surface of the active material layer of the positive electrode sheet of the lithium ion battery, the problem of low energy density of the lithium ion battery is solved, the energy density and stability of the battery are improved, and the thermal safety and high-temperature storage performance of the battery are improved.

CN119518131APending Publication Date: 2025-02-25ZHUHAI COSMX BATTERY CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411352816.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-26
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

Since the first effect of the negative electrode material is lower than that of the positive electrode material, the actual reversible capacity of the battery is lower than that of the positive electrode material, resulting in a low energy density. The existing lithium supplementation method is prone to damage the internal structure of the electrode sheet and deterioration of the interface.

Method used

By providing a lithium supplementary functional layer on the surface of the active material layer of the positive electrode sheet, the functional layer includes lithium quaternary acid, conductive agent and stabilizer. The stabilizer is a lithium-containing inorganic compound with a particle size between 0.1 μm and 3 μm. The diaphragm resistivity and the particle size of lithium quaternary acid meet specific formulas to achieve lithium supplementation for lithium ion batteries.

Benefits of technology

It improves the energy density of lithium-ion batteries, extends the stability and cycle life of the battery, improves the thermal safety performance and high-temperature storage performance of the battery, and stabilizes the decomposition speed of lithium quaternary acid by synergistically acting as a stabilizer, preventing the increase in interface impedance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119518131A_ABST
    Figure CN119518131A_ABST
Patent Text Reader

Abstract

The invention provides a positive plate and a battery, the positive plate comprises a current collector, an active material layer and a functional layer, the active material layer and the functional layer are located on at least one side surface of the current collector, the active material layer is located on one side close to the current collector, and the functional layer is located on one side far away from the current collector; the functional layer comprises lithium squarate, a conductive agent and a stabilizer; the stabilizer is a lithium-containing inorganic compound, the particle size Dv50 of the stabilizer is D1, and 0.1 [mu] m < = D1 < = 3 [mu] m. According to the positive plate disclosed by the invention, the lithium supplement function layer positioned on the surface of the active material layer is arranged, so that lithium supplement of the lithium ion battery can be realized, the energy density is improved, the stability and the cycle life of the battery can be prolonged, the thermal safety performance of the battery is improved, and the high-temperature storage performance of the battery is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of lithium ion batteries, and in particular to a positive electrode sheet and a battery. Background Art

[0002] As a secondary battery, lithium-ion batteries are now widely used in mobile phones, laptops, and electric vehicles due to their high energy density and good charge and discharge cycle capabilities. However, for lithium-ion batteries whose negative electrode material first efficiency is lower than that of the positive electrode material, the active lithium capacity contributed by the positive electrode cannot completely make up for the active lithium capacity consumed by the negative electrode, which will cause the actual reversible capacity of the lithium-ion battery to be lower than the reversible capacity of the positive and negative electrode materials, resulting in a low energy density of the battery.

[0003] At present, in order to make up for the energy density loss caused by the insufficient first effect of the negative electrode material, the negative electrode material or the negative electrode sheet is usually pre-lithiated. In the way of pre-lithiation of the negative electrode material, if the pre-lithiation amount is too high, it is easy to cause the stability of the negative electrode material to deteriorate. If the pre-lithiation amount is controlled at a lower level, a higher energy density cannot be obtained. Moreover, lithium strips or lithium powders are usually used for pre-lithiation of the negative electrode material, which has very strict requirements on environmental moisture control and safety hazards. Therefore, it is necessary to provide a new idea to improve the above problems. In the prior art, a positive electrode lithium supplement is used to supplement the active lithium of the entire battery. It is usually directly added to the positive electrode active material to prepare a slurry and coat it into a positive electrode sheet. However, this method will cause the internal structure of the electrode sheet to be damaged, especially the conductive network of the electrode sheet will be impacted by the gas, and it will also lead to an increase in the thickness of the active material layer. Moreover, after some positive electrode lithium supplements produce gas during the decomposition process, it is easy to cause the interface to deteriorate and the interface impedance to increase, which will affect the long-term stability and cycle life of the battery. Summary of the invention

[0004] Based on the above problems, the present invention provides a positive electrode sheet and a battery. The positive electrode sheet can replenish lithium for lithium-ion batteries and improve energy density by setting a lithium replenishment functional layer on the surface of the active material layer. At the same time, it can also extend the stability and cycle life of the battery, enhance the thermal safety performance of the battery, and improve the high-temperature storage performance of the battery.

[0005] To achieve the above purpose, the technical solution adopted by the present invention is as follows:

[0006] A first aspect of the present invention provides a positive electrode sheet, comprising a current collector and an active material layer and a functional layer located on at least one side of the current collector, wherein the active material layer is located on a side close to the current collector, and the functional layer is located on a side away from the current collector;

[0007] The functional layer comprises lithium squarate, a conductive agent and a stabilizer;

[0008] The stabilizer is a lithium-containing inorganic compound, and the particle size Dv50 of the stabilizer is D1, 0.1 μm≤D1≤3 μm;

[0009] The film resistivity of the functional layer is ρ1, with a unit of Ω·cm; the particle size Dv50 of the lithium squarate is D2, with a unit of μm; and ρ1 and D2 satisfy the following formula: ρ1×D2≤500.

[0010] A second aspect of the present invention provides a battery, comprising the positive electrode sheet described in the first aspect of the present invention.

[0011] Through the above technical solution, the present invention has at least the following advantages compared with the prior art:

[0012] The positive electrode provided by the present invention can replenish lithium for lithium-ion batteries and improve energy density by providing a lithium replenishing functional layer located on the surface of the active material layer. At the same time, it can also extend the stability and cycle life of the battery, enhance the thermal safety performance of the battery, and improve the high-temperature storage performance of the battery. Furthermore, the stabilizer in the functional layer of the positive electrode can play a synergistic role with the lithium replenishing agent lithium squarate, so that the decomposition rate of lithium squarate is more stable, and the interface contact is prevented from being deteriorated due to excessive decomposition of lithium squarate, while the increase of interface impedance is suppressed, and the adverse effect on the electrical performance of the battery is reduced. Moreover, the stabilizer in the functional layer can continuously release lithium ions in subsequent cycles, and the lithium replenishing effect is more lasting, further improving the cycle life and cycle stability of the battery.

[0013] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] Figure 1 A schematic structural diagram of a positive electrode sheet according to an embodiment of the present invention.

[0015] Figure 2 This is a SEM image of the surface of the positive electrode sheet according to an embodiment of the present invention.

[0016] Description of reference numerals:

[0017] Current collector-1, active material layer-2, functional layer-3. DETAILED DESCRIPTION

[0018] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.

[0019] In the detailed description and claims, a list of items connected by the terms "at least one of," "at least one of," "at least one of," or other similar terms may mean any combination of the listed items. For example, if items A and B are listed, the phrase "at least one of A and B" means only A; only B; or A and B. In another example, if items A, B, and C are listed, the phrase "at least one of A, B, and C" means only A; or only B; only C; A and B (excluding C); A and C (excluding B); B and C (excluding A); or all of A, B, and C. Item A may include a single element or multiple elements. Item B may include a single element or multiple elements. Item C may include a single element or multiple elements.

[0020] The positive and negative electrode materials of lithium batteries each have their own first coulombic efficiency (referred to as first efficiency), which is usually less than 100%. For conventional lithium battery positive electrode materials (lithium iron phosphate, lithium cobalt oxide, ternary materials, etc.), the capacity of the first lithium that can be extracted is higher than the capacity of the first lithium that can be embedded. The capacity difference here represents the active lithium capacity that the positive electrode can contribute (and the capacity of the first lithium that can be embedded here usually represents the reversible capacity of the positive electrode material). For conventional lithium battery negative electrode materials (graphite, silicon-based materials, etc.), the capacity of the first lithium that can be embedded is higher than the capacity of the first lithium that can be extracted. The capacity difference here represents the active lithium capacity that the negative electrode needs to consume (and the capacity of the first lithium that can be extracted here usually represents the reversible capacity of the negative electrode material). Considering that the ratio of negative electrode capacity / positive electrode capacity is usually equal to 1 or slightly greater than 1, when the first efficiency of the positive electrode material is equivalent to the first efficiency of the negative electrode material, the active lithium capacity that the positive electrode can contribute can just make up for the active lithium capacity that the negative electrode needs to consume. At this time, the battery maximizes the reversible capacity of the positive and negative electrode materials, and the battery has the highest energy density. However, for lithium batteries whose negative electrode materials have a lower initial efficiency than positive electrode materials, the active lithium capacity contributed by the positive electrode cannot completely make up for the active lithium capacity consumed by the negative electrode, resulting in the actual reversible capacity of the battery being lower than the reversible capacity of the positive and negative electrode materials, and the battery's energy density is low. Therefore, in order to make up for the energy density loss caused by the insufficient initial efficiency of the negative electrode material, the entire battery needs to be supplemented with active lithium.

[0021] Based on the above problems, the first aspect of the present invention provides a positive electrode sheet, the structural schematic diagram of which is as follows Figure 1 As shown, it includes a current collector 1 and an active material layer 2 and a functional layer 3 located on at least one side of the current collector 1, wherein the active material layer 2 is located on a side close to the current collector 1, and the functional layer 3 is located on a side away from the current collector 1;

[0022] The functional layer comprises lithium squarate, a conductive agent and a stabilizer;

[0023] The stabilizer is a lithium-containing inorganic compound, and the particle size Dv50 of the stabilizer is D1, satisfying 0.1 μm≤D1≤3 μm;

[0024] The film resistivity of the functional layer is ρ1, with a unit of Ω·cm; the particle size Dv50 of the lithium squarate is D2, with a unit of μm; and ρ1 and D2 satisfy the following formula: ρ1×D2≤500.

[0025] In the present invention, the active material layer 2 and the functional layer 3 are sequentially arranged on at least one side surface of the current collector 1, and the lithium squarate and other auxiliary agents that play a role in replenishing lithium are all contained in a specific functional layer. Compared with the positive electrode sheet that is directly added to the active material layer slurry to prepare the coating together, it will not affect the internal structure of the positive electrode active material in the active material layer. This is because lithium squarate and other lithium replenishers will decompose when the battery is first formed and charged, and the released active lithium can play a role in replenishing lithium, but at the same time, it will decompose and produce gas. If this gas is produced in the active material layer, it will cause the internal structure of the electrode sheet to be damaged, especially the conductive network of the electrode sheet will be impacted by the gas; moreover, lithium squarate and other lithium replenishers are mixed in the active material layer. Since the lithium replenisher material itself occupies the volume in the active material layer, the thickness of the active material layer will increase, and even after the lithium replenisher is formed, charged and decomposed, pores will still be left to continue to occupy the volume. The present invention adopts the method of setting up separate functional layers, and lithium squarate and its additives with lithium supplement function are concentratedly coated on the surface of the active material layer, so that decomposition and gas production will not impact the active material layer; at the same time, the lithium squarate and its additives in the functional layer will cause the functional layer structure to "collapse" after the surface decomposition, and the thickness of the active material layer and the functional layer on the surface of the current collector will also decrease accordingly, thereby avoiding the functional layer's occupation of volume as much as possible, which is conducive to lithium-ion batteries to obtain higher energy density.

[0026] Further, in the present invention, the functional layer comprises lithium quartz, a conductive agent and a stabilizer. Different from other lithium supplements, the products after decomposition are large in volume, which are easy to cause loss of battery energy density. The lithium quartz provided by the functional layer of the present invention, as a lithium supplement, is mainly gas and amorphous carbon with a small volume after decomposition, so it can ensure that the impact on battery energy density is small; and the stabilizer in the functional layer of the positive electrode provided by the present invention can play a synergistic role with lithium quartz, so that the decomposition rate of lithium quartz is more stable, preventing lithium quartz from decomposing too quickly and causing deterioration of interface contact, while suppressing the increase of interface impedance and reducing the adverse effect on electrical performance; and the stabilizer in the functional layer can continuously release lithium ions in subsequent cycles, and the lithium supplement effect is more lasting, further improving the battery cycle life and cycle stability.

[0027] Furthermore, in the present invention, the stabilizer is a lithium-containing inorganic compound, and the particle size Dv50 of the stabilizer is D1, which satisfies 0.1μm≤D1≤3μm. For example, the value of D1 can be 0.1μm, 0.2μm, 0.3μm, 0.4μm, 0.5μm, 0.6μm, 0.7μm, 0.8μm, 0.9μm, 1μm, 1.2μm, 1.4μm, 1.6μm, 1.8μm, 2μm, 2.1μm, 2.3μm, 2.5μm, 2.7μm, 2.9μm, 3μm. When the small-particle lithium-containing inorganic compound is used as a stabilizer, it can ensure full contact with lithium squarate, so as to better play the stabilizing effect of the stabilizer on lithium squarate, adjust the decomposition rate of lithium squarate, and then avoid the increase of interface impedance, and further reduce the adverse effect on the electrical performance of lithium ion batteries. In a preferred embodiment, 0.1 μm ≤ D1 ≤ 1.5 μm.

[0028] In addition, in the present invention, the film resistivity of the functional layer is ρ1, in units of Ω·cm; the particle size Dv50 of the lithium squarate is D2, in units of μm; the ρ1 and the D2 satisfy the following formula: ρ1×D2≤500. Among them, the film resistivity is a physical quantity that describes the conductivity of the film material, which reflects the resistance per unit length and per unit area of ​​the film surface. The film resistivity ρ1 of the functional layer represents the resistivity of the functional layer film material, which is the resistivity when the functional layer film is tested alone. It should be noted that the decomposition of the lithium supplement is electrochemical decomposition, and there are two indispensable conditions: ① the voltage reaches the decomposition voltage; ② continuous good electrical contact (unobstructed electron transmission path), so whether the decomposition of the lithium supplement lithium squarate is sufficient or not is directly related to whether the electronic conductivity of the functional layer is good. The higher the film resistivity of the functional layer, the less sufficient the decomposition of the lithium supplement lithium squarate is, and the worse the lithium supplement effect will be. At the same time, in order to maintain good electrical contact, the particle size D2 of the lithium squarate is also very critical; therefore, the present invention simultaneously adjusts the particle size D2 and the functional layer of the lithium supplement lithium squarate. The membrane resistivity ρ1 of the energy layer satisfies the above formula, which can ensure the effective decomposition of the lithium supplement lithium squarate, make it decompose more fully and without residue, and in order to ensure that the voltage reaches the decomposition voltage, the larger the membrane resistivity ρ1 of the functional layer, the smaller the particle size D2 of the lithium supplement lithium squarate is required, and the smaller the membrane resistivity ρ1, the larger the particle size D2 of the lithium supplement lithium squarate can be. Moreover, when ρ1×D2≤500 is met, the optimal decomposition voltage can be reached and good electrical contact can be maintained, thereby realizing the efficient decomposition of the lithium supplement lithium squarate.

[0029] Specifically, the film resistivity ρ1 of the functional layer is measured using the BER2500 series electrode resistance meter test equipment of Yuanneng Technology (Xiamen) Co., Ltd.; the specific method is: the functional layer is coated on the surface of 5μm copper foil to obtain a single-sided coated sample, and then the sample is tested with the above test equipment. During the test, the two probes of the equipment apply a pressure of 5MPa to the sample. ρ1=RS / L, R is the impedance of the equipment test, S is the area of ​​the test probe, and L is the thickness of the functional layer, and the film resistivity ρ1 of the functional layer can be obtained.

[0030] Specifically, "Dv50" refers to the particle size corresponding to when the cumulative volume particle size distribution percentage of a sample reaches 50%. Dv50 can be tested using a Malvern laser particle size analyzer.

[0031] In a specific embodiment, the membrane resistivity of the active material layer is ρ2, in units of Ω·cm; the ρ1 and the ρ2 satisfy the following formula: ρ1 / ρ2≤0.8. It should be noted that the membrane resistivity ρ1 of the active material layer represents the resistivity of the membrane material of the active material layer, which is the resistivity of the membrane of the active material layer tested separately. The lower membrane resistivity of the functional layer is conducive to the lithium quartz to exert a higher lithium replenishment effect and obtain a higher positive electrode gram capacity. By further adjusting the ratio of the membrane resistivity ρ2 and ρ1 of the active material layer to satisfy ρ1 / ρ2≤0.8, a better lithium replenishment effect can be obtained. Because the functional layer does not directly contact the current collector, its electronic conduction needs to go through a longer path, so the requirements for electronic conductivity are higher, but lithium quartz itself is an electronic insulating material with slightly poor electronic conductivity, so it will restrict the electrochemical decomposition of lithium quartz. Therefore, the design of the present invention makes the functional layer film resistivity ρ1 lower than the active material layer film resistivity ρ2, which can make the electronic conductivity of the functional layer better than that of the active material layer, and is more conducive to the decomposition of lithium succinate in the functional layer.

[0032] In a specific embodiment, the porosity of the functional layer is P1, in %; P1, D1 and D2 satisfy the following formula: 1 / 600≤P1D2 / D1≤5. The larger porosity of the functional layer is conducive to the rapid removal of the gas generated by the decomposition of lithium squarate, and the porosity of the functional layer is related to the particle size of lithium squarate and the stabilizer in the functional layer, so by adjusting the relationship between P1, D1 and D2 to satisfy the above relationship, the removal rate of the gas generated by the decomposition of lithium squarate can be further improved.

[0033] Furthermore, in a preferred embodiment, the porosity of the active material layer is P2, in %; P1 and P2 satisfy the following formula: P2 / P1<1. When the porosity of the active material layer and the porosity of the functional layer satisfy the above formula, the porosity of the positive electrode active material layer can be ensured to be smaller and the compaction density is better, which is beneficial to improving the energy density of the battery, and at the same time, it can further avoid the porosity in the functional layer being too small, which affects the exhaust effect.

[0034] In a specific embodiment, the particle size Dv50 of the lithium squarate satisfies 0.1μm≤D2≤3μm; illustratively, the particle size Dv50 of the lithium squarate can be 0.1μm, 0.2μm, 0.3μm, 0.4μm, 0.5μm, 0.6μm, 0.7μm, 0.8μm, 0.9μm, 1μm, 1.5μm, 2μm, 2.5μm, 3μm; in a preferred embodiment, 0.1μm≤D2≤0.8μm.

[0035] In a specific embodiment, the diaphragm resistivity ρ1 of the functional layer satisfies 0.1Ω·cm≤ρ1≤100Ω·cm; illustratively, the diaphragm resistivity ρ1 of the functional layer may be 0.1Ω·cm, 1Ω·cm, 2Ω·cm, 3Ω·cm, 4Ω·cm, 5Ω·cm, 6Ω·cm, 7Ω·cm, 8Ω·cm, 9Ω·cm, 10Ω·cm, 11Ω·cm, 12Ω·cm, 13Ω·cm, 14Ω·cm, 15Ω·cm, 16Ω·cm, 17Ω·cm, 18Ω·cm, 19Ω·cm, 20Ω·cm, 30Ω·cm, 40Ω·cm, 50Ω·cm, 60Ω·cm, 70Ω·cm, 80Ω·cm, 90Ω·cm, or 100Ω·cm; in a preferred embodiment, 1Ω·cm≤ρ1≤20Ω·cm.

[0036] In a specific embodiment, the diaphragm resistivity ρ2 of the active material layer satisfies 10Ω·cm≤ρ2≤500Ω·cm; illustratively, the diaphragm resistivity ρ2 of the active material layer may be 10Ω·cm, 20Ω·cm, 30Ω·cm, 40Ω·cm, 50Ω·cm, 60Ω·cm, 70Ω·cm, 80Ω·cm, 90Ω·cm, 100Ω·cm, 110Ω·cm, 120Ω·cm, 130Ω·cm, 140Ω·cm, 150Ω·cm, 160Ω·cm, 170Ω·cm, 180Ω·cm, 190Ω·cm, 200Ω·cm, 250Ω·cm, 300Ω·cm, 350Ω·cm, 400Ω·cm, 450Ω·cm, 500Ω·cm; in a preferred embodiment, 20Ω·cm≤ρ2≤200Ω·cm.

[0037] In a specific embodiment, the porosity P1 of the functional layer satisfies 10%≤P1≤60%. Exemplarily, the porosity P1 of the functional layer can be 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%; in a preferred embodiment, 15%≤P1≤30%.

[0038] In a specific embodiment, the porosity P2 of the active material layer satisfies 10%≤P2≤40%. Exemplarily, the porosity P2 of the active material layer can be 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24%, 25%, 30%, 35%, 40%; in a preferred embodiment, 10%≤P2≤20%.

[0039] In a specific embodiment, based on the total mass of the functional layer, the mass content of the stabilizer is 0.01% to 10%. For example, the mass content of the stabilizer can be 0.01%, 0.02%, 0.03%, 0.04%, 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%; the stabilizer can make the decomposition rate of lithium quartz more stable, prevent the decomposition of lithium quartz too fast to cause the interface contact to deteriorate, and at the same time inhibit the increase of interface impedance and reduce the adverse effect on electrical properties. The stabilizer is a small particle lithium-containing inorganic compound. In a preferred embodiment, the mass content of the stabilizer is 0.2% to 5%.

[0040] In a specific embodiment, the oxygen content in the functional layer of the positive electrode sheet after formation is x, which satisfies 0.3%≤x≤10%. For example, the oxygen content in the functional layer can be 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%; the oxygen content in the functional layer can be measured by high temperature combustion method using an element analyzer to obtain the content of oxygen (O) element. The product of lithium supplementation agent lithium quartz after complete decomposition is amorphous carbon, but some intermediate products of insufficient carbonization will also be produced during the reaction, and these products partially contain oxygen. Therefore, by measuring the oxygen content in the functional layer of the positive electrode after formation, it can be reflected whether the decomposition of the lithium supplementing agent lithium squarate is complete, that is, it can reflect the lithium supplementing effect of the lithium supplementing agent lithium squarate. Therefore, the present invention can ensure that the lithium supplementing effect of the lithium supplementing agent lithium squarate is better and the cycle life is better by controlling the oxygen content of the functional layer in the positive electrode after formation within an appropriate range. In a preferred embodiment, 0.3%≤x≤5%.

[0041] In a specific embodiment, the functional layer of the positive electrode sheet after chemical formation has D / I G , satisfying 0.4≤I D / I G ≤3, exemplary, I D / I G It can be 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1, 1.5, 2, 2.5, 3. It should be noted that I D / I G The intensity ratio of the D peak to the G peak in the Raman spectrum test (the test method is to use data processing software (such as Origin) to perform baseline correction and multi-peak fitting on the obtained Raman spectrum, respectively obtain the intensity or area of ​​the D peak and the G peak, and then calculate the intensity or area ratio of the D peak and the G peak according to the fitting result), which can be used to reflect the regularity of the amorphous carbon of the decomposition product of lithium squarate. The higher the regularity of the decomposition product carbon, the more fully the decomposition of the lithium squarate decomposition agent lithium squarate is. Therefore, the present invention further controls the intensity ratio of the D peak to the G peak of the positive electrode functional layer after formation. D / I G Within a suitable range, it is beneficial to further improve the cycle life of the battery. Preferably, 0.4≤I D / I G ≤2.

[0042] According to the positive electrode sheet of the present invention, the lithium quartz is also coated with a coating agent, and the coating agent includes at least one of aluminum oxide, zirconium oxide, titanium oxide, silicon oxide, cerium oxide, aluminum titanate, aluminum phosphate, lithium titanate, lithium phosphate, lithium fluoride, amorphous carbon, carbon black, graphene, and carbon nanotubes. The present invention can further enhance the lithium conduction at the interface of the lithium quartz by coating a layer of coating agent on the lithium quartz, ensuring the smooth release of active lithium, thereby further improving the decomposition degree of the lithium quartz.

[0043] In a specific embodiment, based on the total mass of the functional layer, the mass content of the coating agent is 0.1% to 20%. For example, the mass content of the coating agent can be 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%. In a preferred embodiment, the mass content of the coating agent is 0.5% to 15%.

[0044] In a specific embodiment, the stabilizer includes at least one of lithium nickel oxide, lithium cobalt oxide, ternary nickel cobalt manganese oxide, ternary nickel cobalt aluminum oxide, lithium nickel manganese oxide, lithium manganese oxide, lithium-rich manganese-based materials, lithium iron silicate, lithium ferrous sulfate, lithium iron borate, and lithium iron titanate.

[0045] In a specific embodiment, based on the total mass of the functional layer, the mass content of the lithium quarate is 70% to 99%. For example, the mass content of the lithium quarate can be 70%, 71%, 72%, 73%, 74%, 75%, 76%, 77%, 78%, 79%, 80%, 81%, 82%, 83%, 84%, 85%, 86%, 87%, 88%, 89%, 90%, 91%, 92%, 93%, 94%, 95%, 96%, 97%, 98%, 99%. In a preferred embodiment, the mass content of the lithium quarate is 80% to 95%.

[0046] In a specific embodiment, the conductive agent includes at least one of carbon black, graphene, carbon nanotubes, and carbon fibers. Specifically, based on the total mass content of the functional layer, the mass content of the conductive agent is 0.1% to 20%. Exemplarily, the mass content of the conductive agent can be 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%. In a preferred embodiment, the mass content of the conductive agent is 0.5% to 10%.

[0047] According to the positive electrode sheet of the present invention, the functional layer further comprises a binder, and the binder comprises at least one of polyacrylic acid, polyvinylidene fluoride, nitrile rubber, and hydrogenated nitrile rubber. Specifically, based on the total mass content of the functional layer, the mass content of the binder is 0.1% to 10%. Exemplarily, the mass content of the binder can be 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%. In a preferred embodiment, the mass content of the binder is 0.5% to 5%.

[0048] According to the positive electrode sheet of the present invention, the surface density of the functional layer is 0.05 mg / cm 2 ~5mg / cm 2 For example, the surface density of the functional layer can be 0.05 mg / cm 2 , 0.1mg / cm 2 , 0.2mg / cm 2 , 0.3mg / cm 2 , 0.4mg / cm 2 , 0.5mg / cm 2 , 0.6mg / cm 2 , 0.7mg / cm 2 , 0.8mg / cm 2 , 0.9mg / cm 2 , 1mg / cm 2 , 2mg / cm 2 、3mg / cm 2 , 4mg / cm 2 , 5mg / cm 2 In a preferred embodiment, the surface density of the functional layer is 0.5 mg / cm 2 ~3mg / cm 2 .

[0049] According to the positive electrode sheet of the present invention, the thickness of the functional layer is 0.5 μm to 50 μm. For example, the thickness of the functional layer can be 0.5 μm, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, 35 μm, 40 μm, 45 μm, 50 μm. In a preferred embodiment, the thickness of the functional layer is 0.5 μm to 20 μm.

[0050] A second aspect of the present invention provides a battery, comprising the positive electrode sheet described in the first aspect of the present invention.

[0051] The battery of the present invention can be prepared by conventional methods in the art. Specifically, the positive electrode sheet, the separator and the negative electrode sheet can be stacked in sequence, and then a battery cell can be obtained by a stacking or winding process, and then the above battery can be obtained by baking, liquid injection, formation, packaging and other processes. All materials in the present invention can be prepared according to methods known in the art or obtained through commercial channels.

[0052] The present invention will be described in further detail below in conjunction with specific embodiments. It should be understood that the following embodiments are only exemplary descriptions and explanations of the present invention and should not be construed as limiting the scope of protection of the present invention. All technologies implemented based on the above content of the present invention are included in the scope that the present invention is intended to protect.

[0053] Unless otherwise specified, the experimental methods used in the following examples are all conventional methods; the reagents, materials, etc. used in the following examples, unless otherwise specified, can be obtained from commercial channels.

[0054] Example 1

[0055] For preparing a lithium ion battery comprising the positive electrode sheet

[0056] 1. Preparation of positive electrode

[0057] (1) Preparation of active material layer: A uniform lithium cobalt oxide positive electrode slurry is prepared by a double planetary mixer, and then the lithium cobalt oxide positive electrode slurry is coated on the surface of an aluminum foil current collector by an extrusion coater. The obtained electrode sheet includes an aluminum foil current collector and a lithium cobalt oxide positive electrode active material layer covering the surface of the aluminum foil current collector. The mass ratio of the lithium cobalt oxide positive electrode slurry is as follows: lithium cobalt oxide / acetylene black / PVDF / NMP = 98 / 1 / 1 / 40.

[0058] (2) Preparation of functional layer: a uniform functional layer slurry is prepared by a double planetary mixer, and then the functional layer slurry is coated on the surface of the lithium cobalt oxide positive electrode active material layer by a gravure coater, and then rolled by a roller press after drying to obtain a positive electrode sheet, wherein the obtained positive electrode sheet comprises an aluminum foil current collector, a lithium cobalt oxide positive electrode active material layer covering the surface of the aluminum foil current collector, and a functional layer covering the surface of the lithium cobalt oxide positive electrode active material layer. The mass ratio of the functional layer slurry is as follows: lithium squarate / lithium nickel manganese oxide / acetylene black / PVDF / NMP=90 / 1 / 6 / 3 / 120.

[0059] The particle size D1 of the stabilizer lithium nickel manganese oxide is 1.2 μm, the particle size D2 of lithium quartz is 0.8 μm, the thickness of the functional layer is 10 μm, the porosity P1 of the functional layer is 23.3%, the film resistivity ρ1 of the functional layer is 19 Ω·cm, and the surface density of the functional layer is 1 mg / cm 2, the porosity P2 of the positive electrode active material layer is 18.8%, and the film resistivity ρ2 of the positive electrode active material layer is 186Ω·cm. In addition, the surface SEM image of the positive electrode sheet, such as Figure 2 As shown, the surface morphology of the positive electrode sheet in the figure is mainly the surface morphology of the functional layer, the particles with smaller particle size are lithium quartz, and the particles with slightly larger particle size are stabilizer particles.

[0060] 2. Preparation of negative electrode sheet

[0061] A uniform silicon oxide negative electrode slurry is prepared by a double planetary mixer, and then the silicon oxide negative electrode slurry is coated on the surface of the copper foil current collector by an extrusion coater, and then rolled by a roller press after drying to obtain a negative electrode sheet. The mass ratio of the negative electrode slurry is as follows: silicon oxide / carbon nanotubes / acetylene black / CMC / SBR / water = 92 / 2 / 2 / 1 / 3 / 150.

[0062] 3. Preparation of lithium-ion batteries

[0063] The above-mentioned positive electrode sheet and negative electrode sheet are respectively cut, welded, wound, packaged, injected, aged, formed, sealed and sorted to obtain a soft pack battery sample; wherein, the positive electrode sheet after formation is tested for oxygen content x and I in its functional layer D / I G ;

[0064] Among them, I D / I G The test method is to disassemble the sample battery after discharging, wash the positive electrode with dimethyl carbonate solvent and dry it, analyze the carbon in the functional layer of the positive electrode after drying with a Raman spectrometer, and calculate I based on the Raman spectrum analysis results. D / I G ;

[0065] The test method for the oxygen content x in the functional layer is to disassemble the sample battery after discharging, wash the positive electrode sheet with dimethyl carbonate solvent and then dry it, and perform elemental analysis on the carbon in the functional layer of the positive electrode sheet after drying to obtain the oxygen element content x in the carbon. The test results are recorded in Table 1.

[0066] Embodiment 2:

[0067] Example 2 is carried out with reference to Example 1, and the difference from Example 1 is that the lithium squarate in the functional layer of the positive electrode sheet adopts lithium squarate coated with amorphous carbon. Based on the total mass of the functional layer, the mass content of the coating agent is 5.9%, and the mass ratio of the functional layer slurry is as follows: lithium squarate / lithium nickel manganese oxide / acetylene black / PVDF / NMP=90 / 1 / 0.1 / 3 / 120, see Table 1 and Table 2 for details.

[0068] Embodiment 3:

[0069] Example 3 is carried out with reference to Example 1. The difference from Example 1 is that the stabilizer in the functional layer of the positive electrode sheet adopts a lithium-rich manganese-based material. For details, see Table 1 and Table 2.

[0070] Embodiment 4:

[0071] Example 4 is carried out with reference to Example 1, and the difference from Example 1 is that the weight proportion of the stabilizer in the functional layer of the positive electrode sheet is 0.01%. The weight proportion of the functional layer slurry is as follows: lithium squarate / lithium nickel manganese oxide / acetylene black / PVDF / NMP=90.99 / 0.01 / 6 / 3 / 120, see Table 1 and Table 2 for details.

[0072] Embodiment 5:

[0073] Example 5 is carried out with reference to Example 1, and the difference from Example 1 is that the weight proportion of the stabilizer in the functional layer of the positive electrode sheet is 10%. The weight proportion of the functional layer slurry is as follows: lithium squarate / lithium nickel manganese oxide / acetylene black / PVDF / NMP=81 / 10 / 6 / 3 / 120, see Table 1 and Table 2 for details.

[0074] Embodiment 6:

[0075] Example 6 is carried out with reference to Example 1, and the difference from Example 1 is that the weight proportion of the stabilizer in the functional layer of the positive electrode sheet is 20%. The weight proportion of the functional layer slurry is as follows: lithium squarate / lithium nickel manganese oxide / acetylene black / PVDF / NMP=71 / 20 / 6 / 3 / 120, see Table 1 and Table 2 for details.

[0076] Comparative Example 1:

[0077] The difference between Comparative Example 1 and Example 1 is that the positive electrode sheet does not include a functional layer, and the positive electrode sheet includes an aluminum foil current collector and a lithium cobalt oxide positive electrode active material layer covering the surface of the aluminum foil current collector, see Table 1 and Table 2 for details.

[0078] Comparative Example 2:

[0079] The difference between Comparative Example 2 and Example 1 is that there is no stabilizer in the functional layer of the positive electrode sheet, and the mass ratio of the functional layer slurry is as follows: lithium squarate / acetylene black / PVDF / NMP=91 / 6 / 3 / 120, see Table 1 and Table 2 for details.

[0080] Embodiment 7:

[0081] The difference between Example 7 and Example 1 is that the particle size D2 of lithium succinate in the functional layer of the positive electrode sheet is 5 μm, see Table 1 and Table 2 for details.

[0082] Embodiment 8:

[0083] The difference between Example 8 and Example 1 is that the porosity of the functional layer of the positive electrode sheet is 12.1%. The porosity of the functional layer is adjusted by adjusting the pressure during rolling of the electrode sheet. Please refer to Table 1 and Table 2 for details.

[0084] Comparative Example 3:

[0085] The difference between Comparative Example 3 and Example 1 is that the particle size D1 of the stabilizer lithium nickel manganese oxide in the functional layer of the positive electrode sheet is 4 μm, see Table 1 and Table 2 for details.

[0086] Comparative Example 4:

[0087] The difference between Comparative Example 4 and Example 1 is that the film resistivity of the functional layer of the positive electrode sheet is 800Ω·cm. The mass ratio of the corresponding functional layer slurry is as follows: lithium squarate / lithium nickel manganese oxide / acetylene black / PVDF / NMP=90 / 1 / 1 / 8 / 120, see Table 1 and Table 2 for details.

[0088] Table 1

[0089]

[0090]

[0091] Table 2

[0092] Group <![CDATA[ρ1×D2]]> <![CDATA[ρ1 / ρ2]]> <![CDATA[P1D2 / D1]]> <![CDATA[P2 / P1]]> Example 1 15.2 0.1021 0.1553 0.8069 Example 2 9 0.0538 0.0018 0.7769 Example 3 14.4 0.0968 0.1339 0.7490 Example 4 12.8 0.0860 0.1373 0.9126 Example 5 11.2 0.0753 0.1753 0.7148 Example 6 9.6 0.0645 0.1913 0.6551 Comparative Example 1 / / / / Comparative Example 2 16.8 0.1129 / 0.8744 Example 7 90 0.0968 1.1417 0.6861 Example 8 15.2 0.0807 0.054 1.5537 Comparative Example 3 13.6 0.0914 0.0538 0.6989 Comparative Example 4 640 4.3011 0.1447 0.8664

[0093] Lithium-ion battery test example

[0094] The lithium ion batteries obtained in the above examples and comparative examples were tested by the following method, and the test results are recorded in Table 3:

[0095] The test methods for performance parameters are as follows:

[0096] (1) Energy density test

[0097] The sample battery was charged in an environment of 25℃±1℃ according to the following operation process, and then discharged to obtain the discharge energy of the lithium-ion battery: charged to the upper limit voltage at 0.5C constant current, then charged at constant voltage until the current dropped to 0.025C and cut off, let it stand for 5 minutes, discharged to 3.0V at 0.5C constant current, let it stand for 5 minutes, and obtained the discharge energy E. After the above lithium-ion battery charging steps are completed, the length L, width W, and height H of the lithium-ion battery are tested with a laser thickness gauge to obtain the volume V=L×W×H of the lithium-ion battery. Its energy density (ED)=E / V, in units of Wh / L.

[0098] (2) Full battery positive electrode capacity test

[0099] The sample battery was charged and discharged in an environment of 25℃±1℃ according to the following operation process to obtain the discharge capacity of the lithium-ion battery: charged to the upper limit voltage at 0.5C constant current, then charged at constant voltage until the current drops to 0.025C, left to stand for 5 minutes, discharged to 3.0V at 0.5C constant current, left to stand for 5 minutes, and obtained the discharge capacity Q. It is known that the effective positive electrode active material mass in the sample battery is m. The positive electrode gram capacity = Q / m, in units of mAh / g.

[0100] (3) Cycle life test

[0101] Place the sample battery in an environment of 25℃±1℃, discharge at 0.5C constant current to the lower limit voltage (3.0V), and let it stand for 5 minutes; then charge at 0.5C constant current to the upper limit voltage (4.53V), then charge at 4.53V constant voltage until the current drops to 0.025C and stop, let it stand for 5 minutes; then discharge at 0.5C constant current to 3.0V, let it stand for 5 minutes, this is a charge and discharge cycle. Repeat the charge / discharge cycle until the ratio of the discharge capacity to the initial discharge capacity in a certain cycle is ≤80%, and the number of cycles experienced is the cycle life.

[0102] (4) 130℃ furnace temperature test

[0103] The sample battery is charged at a constant current of 0.5C to the upper limit voltage, and then charged at a constant voltage until the current drops to 0.025C and stops charging. Then the sample battery is placed in an oven and heated at an initial temperature of 25°C with a heating rate of 5°C / min. After heating to an oven temperature of 130°C, the temperature is maintained for 60 minutes to observe whether the battery burns or explodes. The passing standard is that the lithium-ion battery does not smoke, catch fire, or explode. A total of 20 sample batteries were tested and the pass rate was calculated.

[0104] (5) 85℃ high temperature storage test

[0105] The sample battery was charged at a constant current of 0.5C to the upper limit voltage, and then charged at a constant voltage until the current dropped to 0.025C, and the charging was stopped, and the battery thickness h0 was tested. Then the sample battery was placed in an 85°C oven for 24 hours. The battery was taken out of the oven and the thickness h1 of the battery was tested, and the battery thickness expansion rate θ = (h1-h0) / h0×100% was calculated.

[0106] Table 3

[0107]

[0108] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A positive electrode sheet, characterized in that: It comprises a current collector and an active material layer and a functional layer located on at least one side of the current collector, wherein the active material layer is located on a side close to the current collector, and the functional layer is located on a side away from the current collector; The functional layer comprises lithium squarate, a conductive agent and a stabilizer; The stabilizer is a lithium-containing inorganic compound, and the particle size Dv50 of the stabilizer is D1, 0.1 μm≤D1≤3 μm; The film resistivity of the functional layer is ρ1, with a unit of Ω·cm; the particle size Dv50 of the lithium squarate is D2, with a unit of μm; and ρ1 and D2 satisfy the following formula: ρ1×D2≤500.

2. The positive electrode sheet according to claim 1, characterized in that: The film resistivity of the active material layer is ρ2, with a unit of Ω·cm; the ρ1 and the ρ2 satisfy the following formula: ρ1 / ρ2≤0.

8.

3. The positive electrode sheet according to claim 1, characterized in that: The porosity of the functional layer is P1, in %; P1, D1 and D2 satisfy the following formula: 1 / 600≤P1D2 / D1≤5; Preferably, the porosity of the active material layer is P2, in %; P1 and P2 satisfy the following formula: P2 / P1<1.

4. The positive electrode sheet according to claim 1, characterized in that: The particle size Dv50 of the lithium squarate satisfies 0.1 μm≤D2≤3 μm, preferably 0.1 μm≤D2≤0.8 μm; and / or, the film resistivity ρ1 of the functional layer satisfies 0.1Ω·cm≤ρ1≤100Ω·cm, preferably, 1Ω·cm≤ρ1≤20Ω·cm; and / or, the sheet resistivity ρ2 of the active material layer satisfies 10Ω·cm≤ρ2≤500Ω·cm, preferably, 20Ω·cm≤ρ2≤200Ω·cm; And / or, the porosity P1 of the functional layer satisfies 10%≤P1≤60%, preferably, 15%≤P1≤30%; And / or, the porosity P2 of the active material layer satisfies 10%≤P2≤40%, preferably, 10%≤P2≤20%.

5. The positive electrode sheet according to claim 1, characterized in that: Based on the total mass of the functional layer, the mass content of the stabilizer is 0.01% to 10%, preferably 0.2% to 5%.

6. The positive electrode sheet according to claim 1, characterized in that: The oxygen content in the functional layer of the positive electrode sheet after formation is x, which satisfies 0.3%≤x≤10%, preferably 0.3%≤x≤5%; And / or, the functional layer of the positive electrode sheet after chemical formation, wherein D / I G , satisfying 0.4≤I D / I G ≤3, preferably 0.4≤I D / I G ≤2.

7. The positive electrode sheet according to claim 1, characterized in that: The lithium quartz is also coated with a coating agent, and the coating agent includes at least one of aluminum oxide, zirconium oxide, titanium oxide, silicon oxide, cerium oxide, aluminum titanate, aluminum phosphate, lithium titanate, lithium phosphate, lithium fluoride, amorphous carbon, carbon black, graphene, and carbon nanotubes; Preferably, based on the total mass of the functional layer, the mass content of the coating agent is 0.1% to 20%, preferably 0.5% to 10%.

8. The positive electrode sheet according to claim 1, characterized in that: The stabilizer includes at least one of lithium nickel oxide, lithium cobalt oxide, ternary nickel cobalt manganese oxide, ternary nickel cobalt aluminum oxide, lithium nickel manganese oxide, lithium manganese oxide, lithium-rich manganese-based materials, lithium iron silicate, lithium ferrous sulfate, lithium iron borate, and lithium iron titanate; And / or, the conductive agent includes at least one of carbon black, graphene, carbon nanotubes, and carbon fibers; And / or, the functional layer further comprises a binder, and the binder comprises at least one of polyacrylic acid, polyvinylidene fluoride, nitrile rubber, and hydrogenated nitrile rubber.

9. The positive electrode sheet according to claim 1, characterized in that: The surface density of the functional layer is 0.05 mg / cm 2 ~5mg / cm 2 , preferably 0.5 mg / cm 2 ~3mg / cm 2 ; And / or, the thickness of the functional layer is 0.5 μm to 50 μm, preferably 0.5 μm to 20 μm.

10. A battery, characterized in that: The battery comprises the positive electrode sheet according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Positive pole piece of lithium ion battery, and production method and application thereof

    CN112151889A

  • Positive electrode containing lithium supplement composition, preparation method of positive electrode and lithium ion battery

    CN115939309A

  • Secondary battery and electric device

    CN118039790A

  • Modified lithium squarate as well as preparation method and application thereof

    CN118198362A

  • Lithium supplement electrode plate and preparation process thereof

    CN118610378A